Pendidikan yang Memerdekakan Peserta Didik Dengan Menerapkan Sistem Among di Sekolah Dasar - M, Murvita; M, Melisah; Nur, Nikmatun; Rahmawati, Kunti; Saphira, Grazella Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education in Indonesia still focuses heavily on achieving grades and memorization, so it does not give students the freedom to learn independently and creatively. This causes the independence of education for students to be constrained. Education that liberates students is a concept that prioritizes independence and freedom of learning for students. The Among system, a traditional Javanese education system based on the philosophy of Ki Hajar Dewantara, has the potential to realize education that liberates students. Where this system has the potential to realize education that liberates students in elementary schools. The method used in this study is a literature study by collecting data from previous research results and their relevant results. The purpose of the literature study in this study is 1) to find the problem to be studied, 2) to find information and data that are relevant to the topic to be discussed, 3) to add new knowledge from the results of the research being studied, 4) to test a basic truth of the theoretical approach in the problem being studied. While the analysis technique used is content analysis. The results of this study indicate that the among system is considered effective in realizing education that liberates students.